1994
DOI: 10.1038/368239a0
|View full text |Cite
|
Sign up to set email alerts
|

Facial shape and judgements of female attractiveness

Abstract: The finding that photographic and digital composites (blends) of faces are considered to be attractive has led to the claim that attractiveness is averageness. This would encourage stabilizing selection, favouring phenotypes with an average facial structure. The 'averageness hypothesis' would account for the low distinctiveness of attractive faces but is difficult to reconcile with the finding that some facial measurements correlate with attractiveness. An average face shape is attractive but may not be optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
448
1
25

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 728 publications
(498 citation statements)
references
References 18 publications
18
448
1
25
Order By: Relevance
“…This is significant, as previous studies have demonstrated that prototypicality impacts on perceptions of attractiveness, whereby averageness increases attractiveness (though the most attractive faces are not necessarily average; Langlois and Roggman 1990;Perrett et al 1994;DeBruine et al 2007). The current study presented participants with male faces that were manipulated to range in sexual dimorphism from −100% to +200% of masculinity, including the original, unmanipulated masculinity level (0%).…”
Section: Resultsmentioning
confidence: 86%
“…This is significant, as previous studies have demonstrated that prototypicality impacts on perceptions of attractiveness, whereby averageness increases attractiveness (though the most attractive faces are not necessarily average; Langlois and Roggman 1990;Perrett et al 1994;DeBruine et al 2007). The current study presented participants with male faces that were manipulated to range in sexual dimorphism from −100% to +200% of masculinity, including the original, unmanipulated masculinity level (0%).…”
Section: Resultsmentioning
confidence: 86%
“…Feminine female faces (versus masculine female faces) are typically represented by specific features such as tall and wide eyes, full lips, small lower face area (e.g., small chin), thin eyebrows, and high cheekbones 1 (Cunningham, 1986;Cunningham et al, 1995;Johnston, 2006;Johnston & Franklin, 1993;Perrett, May, & Yoshikawa, 1994).…”
Section: Men's Preferences For Facial Femininitymentioning
confidence: 99%
“…To facilitate the investigation of face processing, Perrett and his colleagues (e.g., Perrett, May, & Yoshikawa, 1994) have created a large data base of face stimuli, which has been widely used in research. We adopted some of these stimuli, which had been previously rated for the relevant social attributes to form two of the sets of images we used.…”
Section: Experimental Tasksmentioning
confidence: 99%